Factors Related to the Level of Anxiety of People in Landslide-Prone Areas in Parongpong District - Syifa Nur Atiyah; Gilny Aileen Joan (Interdisciplinary Social Studies, 2025)
Natural disasters, such as landslides, can cause significant psychological impacts, such as anxiety. Anxiety is a mental disorder characterized by feelings of fear, worry, restlessness, and physical symptoms such as increased blood pressure, trembling, and headaches. This study aims to identify the factors that influence the level of anxiety among communities in landslide-prone areas, particularly in the Parongpong District, West Bandung Regency. The study uses a quantitative correlational method with a cross-sectional approach. The research population consists of the community in Parongpong District, with a sample of 70 individuals selected using purposive sampling techniques. The variables analyzed include age, gender, educational background, experience of being affected by a disaster, disaster training, and length of residence. The analysis of 70 respondents with diverse characteristics (26 males and 44 females) shows that most respondents experience mild anxiety, with an average score of 6 on the GAD-7 scale. Of the respondents, 49 (70%) experienced mild anxiety, 16 (22.8%) experienced moderate anxiety, 1 (1.4%) experienced severe anxiety, and 4 (5.7%) did not experience anxiety. Factors such as age, gender, educational background, experience of being affected by a disaster, disaster training, and length of residence did not show a significant relationship with the level of anxiety (p > 0.05). These findings are consistent with previous research that shows the psychosocial impacts of landslides, but with relatively low anxiety levels in the Parongpong District. This study recommends the integration of mental health programs into disaster mitigation policies and an increase in community preparedness. A holistic approach involving the government, health workers, and the community is needed to build resilience against disasters, not only physically but also psychologically.